Studi Empiris Evaluasi Performa Website IAIN Salatiga Menggunakan Automated Software Testing - Suprapto, Agung; Sasongko, Dimas (STIKOM Tunas Bangsa Pematangsiantar, 2021)
The purpose of this study is to determine the performance of the loading speed of the website, identify the factors that affect the test results, and suggest improvements that can be made to improve the loading speed performance of the IAIN Salatiga website. The research was conducted in four main stages, namely: website traffic observation, designing website performance testing scenarios, website performance testing, and website testing data analysis. Based on the test results, one of the causes of the poor performance assessment is because most of the load time is used to display the largest content on the website. Implementing images with the right size and format can improve website performance. The limitation of this study is that the test uses a free version of the application which has limitations in displaying test results. The results of this study can be used by academics and practitioners in the field of website evaluation studies and the findings of this study can be a concern for website developers in building a website.